1991
DOI: 10.1002/cber.19911240519
|View full text |Cite
|
Sign up to set email alerts
|

Metallcarbonyl‐Synthesen, XX. Einfache Methode zur Darstellung von Tc(CO)3‐Komplexen: Synthese und Struktur der neuartigen Technetium(I)‐Clusterverbindung Na[Tc3(CO)9(OCH3)4] mit Cuban‐Struktur

Abstract: Metal Carbonyl Syntheses, XX. – Simple Method for the Preparation of Tc(CO)3 Complexes: Synthesis, Structures, and Reactivity of the Novel Cubane‐Type Cluster Na[Tc3(CO)9(OCH3)4] Carbonyltechnetium complexes of type LTc(CO)3 are accessible along a simple route from Na[Tc3(CO)9(OCH3)4] (2) which represents a novel alkoxy complex of cubane‐type geometry (single‐crystal X‐ray diffraction study). 2 is an isolable product of the incomplete carbonylation of sodium pertechnetate (1) conducted in methanol. Under carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…84 Several other papers mentioned in this review also report "Tc NMR spectra for compounds reported therein. 28 …”
Section: Line Formulamentioning
confidence: 97%
See 3 more Smart Citations
“…84 Several other papers mentioned in this review also report "Tc NMR spectra for compounds reported therein. 28 …”
Section: Line Formulamentioning
confidence: 97%
“…28 Subsequent carbonylation of (6), under more severe conditions (190 atm CO, 230 °C, 2 d), gives (1). This cluster (6) is an attractive starting material for compounds containing the "Tc(CO) 3 + " fragment (see Section 8.5) as it is easily broken up by a proton source.…”
Section: Oxygen and Sulfurmentioning
confidence: 99%
See 2 more Smart Citations
“…The sodium atom is integrated into the cubane structure. Each Tc atom is surrounded by 3 carbonyl groups and 3 oxygens of the methoxy groups in a strongly distorted octahedron [32] (Fig. 14).…”
Section: Technetium(i)mentioning
confidence: 99%